Analysis of Oceanographic Variabels (Temperature, Salinity, Dept) and Food Habits of Spatial Distribution Blue Swimmer Crab in Semarang Waters - Isnawati, Nadiya; Hartoko, Agus; Febrianto, Sigit (Management of Aquatic Resources Journal (MAQUARES), 2023)
The sand characteristik of the Semarang waters becomes one of the suitable habitats for swimming crab. Become Crab live in 2-50 m. The commodity has an attraction for fisherman, because of the high selling price and keeping interest among seafood lovers. High demand for crab in both domestic and non domestic markets encourage crab fisherman to catch large crabs by infrige to allowable sustainable size of crab. The existence of this research encourages efforts to manage crab resources through the aspects of biology, temperature, salinity, depth and crab food habits. The study start on Agust 08, 2019 to September 26, 2019. The purpose of the study was to determine the spatial distribution of temperature, salinity of crab catches, food composition and the relationship of temperature, salinity variables to crab catches. The method used in this research is the survey method, where the crab data is purposive sampling method. The variables used are temperature, salinity and depth. The result of the study found that the spatial distribution of water temperatures ranged from 26-29ºC, salinity ranged from 32 to 36 ‰ and dept ranged from 10 to 30 m, while the result of identification of 14 small crabs obtained that the digestive contents of all crabs were phytoplankton, mollusca, fish, shrimp and non identifiable material. The results of simple linear regression between temperature, salinity, depth with the crab catch each of R2 = 0.108, R2= 0.6814, depth value of R2 = 0,656.